A review of intelligent CNC controller development based on step-NC - Daud, Mohd Elias; Yusof, Yusri; Minhat, Mohamad (2011)
In the contemporary Computer Numeric Controlled (CNC) machine tools of Computer Aided Manufacturing (CAM) and CNC process conducted by a number of inter-related operations and parameters using G Codes and M codes set as RS274 or ISO 6983 standard. However, this programming language does not explicitly relate to each other to have control of arbitrary locations other than the motion of the block-by-block. STEP-NC is the extension to STEP, Standard for Exchange Product model data. This determines the neutral data format for digital information from a product. STEP-NC standard is on how information about CNC machining can be added to parts represented in the STEP product model data. In this paper is to review and explore the making of interoperable CNC manufacturing is then provided relating milling, turning, turn-mill through the development of information models for products, processes and new machining system controller developed base on new standard ISO 14649 standard and ISO 10303, which related to data modeling for CNC features, process planning, and machine tool. It is expected that this paper will meet a step towards the requirements for global interoperable manufacturing for real-life machining system.